From mass to number: A critical review of particle number concentration for a better air quality assessment in India - Fatima khursheed; Andreas C.R. Mayer; Monika Gupta; Mohommad Imran Ahmad; Mariyam Khan; Alfred Lawrence (Atmospheric Environment, 2026)

Coast-O-Matic: an automated shoreline detection method using PlanetScope satellite imagery - Alfred Hewetson; James Lawrence; Ioannis Karmpadakis (Frontiers in Marine Science, 2026)
Multispectral satellite imagery enables routine surveying of the surf zone by discretising the land–sea interface at known water levels, supporting estimates of coastal recession and accretion. The daily revisit of PlanetScope provides near-continuous shoreline observations, increasing temporal resolution relative to traditional tasking. Many existing approaches delineate shorelines by applying a single spectral index threshold, typically NDWI, and contouring the resulting binary mask. We present an alternative, fully probabilistic method. An ensemble of multilayer perceptrons (MLPs) is trained to predict, for each pixel, the probability of “water” versus “land.” The shoreline is then extracted as an isoprobability contour, eliminating the need for a global threshold and allowing spatial variability in sensor response, illumination (e.g., shadows), and local geomorphology to be accommodated. Applied to PlanetScope imagery at Seaford, UK, and evaluated against a height contour referenced to the instantaneous water level, the method achieves a root-mean-square error of ≈7m for scenes with<50% cloud cover. These results indicate that probabilistic pixel wise classification, coupled with high-cadence PlanetScope acquisitions, offers robust shoreline detection suitable for high-frequency coastal monitoring.

Correction to: Exploring the dynamics of human-wildlife conficts in the Sai communal area adjacent to Sengwa wildlife research area, Zimbabwe - Innocent Mahakata; Alfred Mapolisa; Oswell Rusinga; Lawrence Mango (European Journal of Wildlife Research, 2025)

Exploring the dynamics of human-wildlife conflicts in the Sai communal area adjacent to Sengwa wildlife research area, Zimbabwe - Innocent Mahakata; Alfred Mapolisa; Oswell Rusinga; Lawrence Mango (European Journal of Wildlife Research, 2025)

Investigating the temporal dynamics of sub-micron particles and particle-bound transition metals in indoor air of a metropolitan city - Samridhi Dwivedi; Farheen Zehra; Jamson Masih; Tarun Gupta; Alfred Lawrence (Environmental Geochemistry and Health, 2024)

Swine global genomic resources: insights into wild and domesticated populations - Neal R. Benjamin; Richard P. M. A. Crooijmans; Luke R. Jordan; Courtni R. Bolt; Lawrence B. Schook; Kyle M. Schachtschneider; Martien A. M. Groenen; Alfred L. Roca (Mammalian Genome, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Assessment of indoor air quality and their inter-association in hospitals of northern India—a cross-sectional study - Anam Taushiba; Samridhi Dwivedi; Farheen Zehra; Pashupati Nath Shukla; Alfred J. Lawrence (Air Quality, Atmosphere & Health, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Evidence for adaptation of porcine Toll-like receptors - Kwame A. Darfour-Oduro; Hendrik-Jan Megens; Alfred Roca; Martien A. M. Groenen; Lawrence B. Schook (Immunogenetics, 2016)

Increasing Underrepresented Scientists in Cancer Research: The UCSD CURE Program - Lawrence Alfred; Paula R. Beerman; Zunera Tahir; Sheila F. LaHousse; Percy Russell; Georgia Robins Sadler (Journal of Cancer Education, 2011)

The class IId bacteriocin thuricin-17 increases plant growth - Kyung Dong Lee; Elizabeth J. Gray; Fazli Mabood; Woo-Jin Jung; Trevor Charles; Scott R. D. Clark; Anh Ly; Alfred Souleimanov; Xiaomin Zhou; Donald Lawrence Smith (Planta, 2009)

Effects of impoundment on nutrient availability and productivity in lakes - Andreas Matzinger; Roger Pieters; Ken I. Ashley; Gregory A. Lawrence; Alfred WÜest (Limnology and Oceanography, 2007)
We investigate the hydraulic alteration and the effect on primary productivity of the Hugh Keenleyside Dam built at the outlet of the Arrow Lakes (British Columbia, Canada) in 1967. Three dam‐induced hydraulic changes have been identified as relevant: (1) water level increase, (2) leveling of the seasonal outflow, and (3) subsurface release of water from the dam. The potential effect of these alterations on primary productivity were tested with a numerical model supported by field observations. Hydraulic modifications can reduce lake productivity by up to 40%, primarily as a result of altered flow path and allowing nutrients to pass through the reservoir without entering the productive zone near the surface. This productivity loss is comparable to the reduction caused by nutrient retention behind dams constructed upstream of the Arrow Lakes Reservoir. The combined productivity loss from both of these two mechanisms is significant and may well be responsible for the dramatic decline of kokanee ( Oncorhynchus nerka ) observed in the Arrow Lakes Reservoir in the 1990s.